Control of Botrytis cinerea Pers. in “Huascaran” tomato by foliar fertilizer on the coast of Lima, Peru - Casimiro Melgarejo, Hugo Benny (2022)
Botrytis cinerea Pers. (B.C.) is the phytopathogen responsible for a wide range of symptom in crops of great importance, such as tomato. Fungicide application are mainly used to control this pathogen; however, their excessive use leads to the development of resistant strains, environmental pollution, and harmful effects on human health. Thus, the aim of the study was to evaluate the effects of two foliar fertilizers contain copper, zinc, and citric acid to reduce gray mold B.C. damage in “Huascarán” tomato plants. In laboratory conditions, the effects of the foliar fertilizers on the inhibition of mycelial growth at 6 DAI (days after inoculation) with poisoned PDA (Potato Dextrose Agar) medium were evaluated; and in the field conditions, the foliar fertilizers were sprayed by eight weeks varying the application frequency in one and two weeks. The results showed that in laboratory condition the citric acid improved the antifungal activity complementing well with the Cu and Zn particles presenting T3 the better percentage of mycelial growth inhibition. Under field conditions, most of the foliar applications had a significant control of B.C. on foliage but not on flowers and fruits; especially when foliar fertilizers were applied weekly. These results are important to develop strategies to improve disease control and to decrease excessive use of fungicides.